Fundamental relation and automorphism group of very thin Hv-groups. Issue 1 (2nd January 2017) - Hamidi, M.; Ashrafi, A. R.
ABSTRACT: The purpose of this paper is computing the fundamental relations and automorphism groups of very thin H v -groups. In this regards, we first investigate some basic properties of H v -groups and then we show that any given group is isomorphic to the fundamental group of a nontrivial H v -group. The main properties of very thin H v -groups are also investigated and it is proved that every finite very thin H v -group is proper.